Photopharmacology of Proteolysis-Targeting Chimeras: A New Frontier for Drug Discovery - Zeng, Shenxin; Zhang, Hongjie; Shen, Zhengrong; Huang, Wenhai (Frontiers in Chemistry, 2021)
Photopharmacology is an emerging field that uses light to precisely control drug activity. This strategy promises to improve drug specificity for reducing off-target effects. Proteolysis-targeting chimeras (PROTACs) are an advanced technology that engineered to degrade pathogenic proteins, through the ubiquitin-proteasome system for disease treatment. This approach has the potential to target the undruggable proteome via event-driven pharmacology. Recently, the combination strategy of photopharmacology and PROTACs has gained tremendous momentum for its use in the discovery and development of new therapies. This review systematically focuses on PROTAC-based photopharmacology. Herein, we provide an overview of the new and vibrant research on photoPROTACs, discuss the advantages and disadvantages of this approach as a biological tool, and outline the challenges it faces in a clinical setting.